I Never Cry - Domalewski, Piotr; Sobocinski, Piotr jr; Stafiej, Zofia; Preis, Kinga; Jakubik, Arkadiusz (Eureka Video, 2021)
Seventeen-year-old Ola (Zofia Stafiej) travels to Ireland to bring her father's body back to Poland after he died working on a construction site. But never mind her dad, Ola wants to know if he saved money for the car he had promised. In a foreign country all by herself, Ola will have the trip of her lifetime, a journey into the unknown, on which she will try to reconnect with her estranged father. In Ireland, she will come to know a different world and meet people who will change her approach to life. From director Piotr Domalewski, "I Never Cry" is a touching comedy about a rebellious teenage girl with a grudge against her father, who was only ever present in her life through regular money transfers. It is also a piercing, realistic look at the difficulties faced by families separated by emigration, told against the backdrop of the life of Polish workers abroad. [Cover]